Digital Transformation Model and the Role of HR in Indonesian MSMEs - Iskandar, Yusuf (IJBLE Scientific Publications Community Inc., 2023)
This study looks into how important human resources (HR) are to Indonesia's Micro, Small, and Medium-sized Enterprises (MSMEs) as they embark on a digital transformation. The study uses a quantitative method with a sample of 568 participants and focuses on the impact of staff skills, digital strategy, employee retention, and satisfaction. The findings indicate that there are complex interactions at play: employee skills show a negative correlation with the speed at which digital transformation is occurring, but employee retention, satisfaction, and digital strategy have a beneficial impact on both digital transformation and competitiveness in the global market. The study gives HR professionals useful insights and draws attention to the complex factors that will determine MSMEs' digital future. This study adds to the growing body of knowledge on HR and digital transformation by offering insightful recommendations for businesses attempting to navigate the challenging terrain of the Fourth Industrial Revolution.